Molecular docking studies, charge transfer excitation and wave function analyses (ESP, ELF, LOL) on valacyclovir : A potential antiviral drug. (February 2019) - B., Fathima Rizwana; Prasana, Johanan Christian; Muthu, S.; Abraham, Christina Susan
Graphical abstract: Highlights: The molecular structure was optimized and the band gap energy was calculated. UV spectral analysis was made and the charge transfer due to excitation was studied. ESP, ELF and LOL maps generated reveals the charge distribution on the surface. Fukui functions and reactivity descriptors were calculated. Molecular docking studies confirmed the antiviral activity of the compound. Abstract: Valacyclovir is thel -valyl ester prodrug of the antiviral drug acyclovir that exhibits activity against Herpes simplex virus types and varicella zoster virus. An explicit surface analysis on the title compound was carried out theoretically using the wavefunction analyser multiwfn software, inorder to study the reactivity of the compound. The input wavefunction files were generated by Gaussian 09W software using B3LYP/6-311++G(d, p) as the basis set. The structure of the title compound was optimized; wave function analyses and the molecular docking studies were completed. The UV spectrum was experimentally recorded in solvent phase and in addition to it the electronic absorption spectrum of the compound was evaluated by TD-DFT in the gas and solvent phase. The ESP (Electrostatic potential) map points out the surface extremas where the global surface minimum is seen at the oxygen atom with the value −61.5675 and global surface maximum near the hydrogen atom with the value 67.862. The energy band gap obtained from the HOMO-LUMO gap (E = 3.6023 eV) were found to be in agreement with the energy gap (E = 3.6174 eV) calculated using λmax from the UV spectrum. The electron-hole distribution of the molecule indicated a charge transfer within the molecule. Electron Localization Function, Local Orbital Localizer, Thermodynamic functions were discussed. The reactive sites of the compound were studied from the fukui function calculations and chemical descriptors define the reactivity of the molecule on the whole. The antiviral activities of the title compound against various viral proteins (VZV, HSV, Dengue) were studied using molecular docking.